Asuhan Kebidanan Komprehensif Pada Ny. F Dengan Faktor Resiko Umur 36 Tahun Dan Jarak Kehamilan 11 Tahun (Studi Kasus terhadap Ny. F di Puskesmas Jatibogor Kabupaten Tegal) - Rina Sukmawati; Istiqomah Dwi Andari; Riska Arsita Harnawati (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
MMR worldwide according to WHO in 2020 is 295.000 in Indonesia, there are 4.627 cases of AKI in 2020. In Central Java, AKI in 2020 is 98.6/100.000 with the city of Tegal having 29.78% and cases of IMR. Data at the Jatibogor Health Center for cases aged >35 years amounted to 16.7% of 840 people. One of the risk factors for pregancy that causes complications and maternal death is the mother’s age (>35 years) and the interval between preganancies >10 years. The governmen always atrives to improve quality maternal health services, there are several things that the government does, including seeking an adequate number of health workers with the best possible quality, providing health service facilities according to standarts, and mobilizing all levels of society to implement birth planning programs with prevention of complications (P4K). The purpose of this case study was to comprehensively carry out midwifery care for pregnant women, women in childbirt, postpartum women and newborns using midwifery management according to Varney and documentation using the SOAP method. The object of this case is Mrs. F G2 P1 A0 36 years old with normal pregnancy, childbirth and postpartum. This case was described out in October 2022 in the work area of the Jatibogor Health Center. The care was described in its entirety, starting from the TM III pregnant patient (37 weeks plus 5 days and 38 weeks plus 5 days) and normal postpartum (9 hours postpartum to 22 days postpartum). The result obtained were Comprehensive Midwifery Care for Mrs. F from gestational age 37 weeks and 5 days, from delivery to postpartum 22 days postaprtum. The preparation concluded that during pregnancy, childbirth and postpartum Mrs. F goes on normally.